1996
DOI: 10.1128/aac.40.12.2874
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility patterns of some recently established coryneform bacteria

Abstract: The susceptibility patterns of 480 isolates representing six recently defined species of coryneform bacteria (Corynebacterium amycolatum [n = 101], Corynebacterium auris [n = 48], Corynebacterium glucuronolyticum [n = 86], Brevibacterium casei [n = 50], Dermabacter hominis [n = 49], and Turicella otitidis [n = 146]) to 17 antimicrobial agents were determined by an agar dilution method. Most significantly, for C. amycolatum strains the MICs at which 90% of isolates are inhibited were > or = 32 micrograms/ml … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1
8

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(63 citation statements)
references
References 31 publications
5
49
1
8
Order By: Relevance
“…were 0.75 mg/ml and 0.19 mg/l, respectively. Interpretative breakpoints are not available for coryneform bacteria, but our results of decreased susceptibilities to betalactams are in line with the data of Funke et al [3]. We assume from the clinical improvement of our patient that the isolate was susceptible to vancomycin and moxifloxacin.…”
Section: Microbiologysupporting
confidence: 91%
“…were 0.75 mg/ml and 0.19 mg/l, respectively. Interpretative breakpoints are not available for coryneform bacteria, but our results of decreased susceptibilities to betalactams are in line with the data of Funke et al [3]. We assume from the clinical improvement of our patient that the isolate was susceptible to vancomycin and moxifloxacin.…”
Section: Microbiologysupporting
confidence: 91%
“…Corynebacterium aurimucosum is a recently described species isolated from clinical samples whose clinical role in human pathology remains unknown [14]. All of these species have been reported as susceptible to glycopeptides, linezolid, Q/D and daptomycin, but with variable resistance to other antibiotics [1,4], as observed in our study. A recently published report showed that tigecycline is active against several species of corynebacteria [7], as in our study, therefore this antibiotic could be another potential treatment for infections caused by these organisms.…”
Section: Resultsmentioning
confidence: 49%
“…More recently, C. amycolatum appeared as one of the commonest species isolated in clinical laboratories, able to cause several nosocomial infections and frequently showing a resistant phenotype against many antibiotics [8]. Together with these species, C. striatum and C. afermentans were also recognised as human pathogens [2,13], showing a variable antibiotic susceptibility phenotype [4]. Corynebacterium coyleae is a new species of corynebacteria that has been recently described as a human pathogen, phenotypically similar to C. jeikeium, which appears to be usually macrolide-resistant [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maeda et al [11] found that a single dose of 1 g azithromycin was effective in 32 (84.2%) of 38 men with non-mycoplasmal, non-ureaplasmal NGCU. Funke et al [12] consider that MICs of ciprofloxacin covered a broad range. However, the strain described in this report, in particular, is susceptible to the treatment administrated, ciprofloxacin, as was observed from the benign evolution of the patient.…”
Section: Discussionmentioning
confidence: 99%